2019
DOI: 10.1186/s13048-019-0598-x
|View full text |Cite
|
Sign up to set email alerts
|

Persistently elevated alpha-fetoprotein associated with chronic hepatitis B during chemotherapy for malignant ovarian germ cell tumors: a case series and a review of the literature

Abstract: Background: Alpha-fetoprotein (AFP) plays a crucial role in the management of malignant ovarian germ cell tumors (MOGCTs) and is an important reference index for chemotherapy termination. However, a high level of AFP can also be caused by several benign diseases, causing confusion and impacting treatment decisions. Case presentation: We described four patients who were diagnosed with MOGCTs; the histologic subtype in two of them was mixed MOGCTs (yolk sac tumor with mature teratoma), while the rest was immatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…2C and Supplementary Table SIV ). AFP encodes alpha fetoprotein, a plasma protein mainly expressed during foetal life in the yolk sack and liver, and high levels of AFP are present in pregnant women to stop follicular growth ( Zong et al , 2019 ). Concerning DMRT3 , double sex and mab-3-related transcription factor 3, its involvement in sexual development is known, but there is scarce knowledge of its specific role in the ovary, whereas MOV10 gene, encoding an RNA helicase phosphorylated after DNA damage, exerts a role in RNA stability and regulation of the network of mammalian germ cells ( Fu et al , 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…2C and Supplementary Table SIV ). AFP encodes alpha fetoprotein, a plasma protein mainly expressed during foetal life in the yolk sack and liver, and high levels of AFP are present in pregnant women to stop follicular growth ( Zong et al , 2019 ). Concerning DMRT3 , double sex and mab-3-related transcription factor 3, its involvement in sexual development is known, but there is scarce knowledge of its specific role in the ovary, whereas MOV10 gene, encoding an RNA helicase phosphorylated after DNA damage, exerts a role in RNA stability and regulation of the network of mammalian germ cells ( Fu et al , 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…14 Though extremely sensitive but not tumor-specific, 15 elevation of AFP is prognostically important and is an important index for stopping chemotherapy in YST. 16 It is a glycoprotein that is normally produced during gestation by the fetal liver and yolk sac. It has been reported that the lowering level of post-operative serum AFP could be a useful marker for determining if residual cancer cells still exist after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Though extremely sensitive but not tumor‐specific, 15 elevation of AFP is prognostically important and is an important index for stopping chemotherapy in YST 16 . It is a glycoprotein that is normally produced during gestation by the fetal liver and yolk sac.…”
Section: Discussionmentioning
confidence: 99%
“…[2] Particularly, wearable electronics have evolved from simple recording of heart rate and body movements to physiological monitoring of glucose, Na + , K + , Ca 2+ , and pH, [3][4][5][6] as well as other more advanced biomarkers in different body fluids, including sweat, [7] tears, [8] saliva, [9] and interstitial fluid, [10,11] and has greatly expanded the clinician's arsenal for early disease detection.Many current tumor biomarkers are proteins or metabolites that are abundant in cancer cells and are released into the circulatory system. [12,13] Clinically, some are used to identify cancers primarily originating from different organ systems, such as α-fetoprotein for liver cancer and germ cell tumors, [14] ß-2-microglobulin for chronic lymphocytic leukemia, [15] calcitonin for medullary thyroid cancer, [16] and prostate-specific antigen for prostate cancer. [17] Despite the wide use of these biomarkers for cancer diagnostics, these protein-based tumor markers are typically detectable at the late stages of cancer progression, [18] when the efficacy of many cancer treatments is substantially compromised.…”
mentioning
confidence: 99%
“…Many current tumor biomarkers are proteins or metabolites that are abundant in cancer cells and are released into the circulatory system. [12,13] Clinically, some are used to identify cancers primarily originating from different organ systems, such as α-fetoprotein for liver cancer and germ cell tumors, [14] ß-2-microglobulin for chronic lymphocytic leukemia, [15] calcitonin for medullary thyroid cancer, [16] and prostate-specific antigen for prostate cancer. [17] Despite the wide use of these biomarkers for cancer diagnostics, these protein-based tumor markers are typically detectable at the late stages of cancer progression, [18] when the efficacy of many cancer treatments is substantially compromised.…”
mentioning
confidence: 99%